2015
DOI: 10.1017/jmo.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Strategy implementation: What is the failure rate?

Abstract: It is often claimed that 50 to 90 percent of strategic initiatives fail. Although these claims have had a significant impact on management theory and practice, they are controversial. We aim to clarify why this is the case. Towards this end, an extensive review of the literature is presented, assessed, compared and discussed. We conclude that whilst it is widely acknowledged that the implementation of a new strategy can be a difficult task, the true rate of implementation failure remains to be determined. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 104 publications
(219 reference statements)
1
70
0
5
Order By: Relevance
“…This is supported by many studies findings and literature views. The study of Candido et al [12] confirmed the difficulty of successfully implementing new business strategies. This perspective had long been recognized in the literature and concluded that most managers believe that the difficulty of implementing strategy surpasses that of formulating it.…”
Section: Strategy Plan Implementationmentioning
confidence: 95%
“…This is supported by many studies findings and literature views. The study of Candido et al [12] confirmed the difficulty of successfully implementing new business strategies. This perspective had long been recognized in the literature and concluded that most managers believe that the difficulty of implementing strategy surpasses that of formulating it.…”
Section: Strategy Plan Implementationmentioning
confidence: 95%
“…Apesar da sobrestimação frequente das taxas de insucesso de métodos e técnicas de gestão (Cândido e Santos, 2015), incluindo a sobrestimação das taxas de insucesso de ferramentas de gestão da qualidade (Cândido e Santos, 2011), considera-se importante ilustrar com algum detalhe a proposta metodológica idealizada na Secção 3.1 e ilustrada na Figura 1. Descreve-se uma forma possível de aplicação da metodologia e não a única forma possível.…”
Section: Proposta Metodológicaunclassified
“…Pesquisadores reportam uma taxa que varia entre 50 e 90% dos planos não realizam plenamente suas expectativas e ambições (Cândido & Santos, 2015).…”
Section: O Desafio Da Implementação Estratégicaunclassified
“…Uma vez que os planejadores não teriam como prever e definir todos os pormenores da estratégia, exigindo alguns ajustes incrementais, a partir da identificação e solução dos problemas que surgem no decorrer do processo (Lê & Jarzabkowski, 2015 Fischmann (1987), baseado em Bonoma (1984) Embora pareça haver uma crescente conscientização sobre a importância da implementação, corroborada pelo aumento de publicações sobre o tema (conforme representado no Figura 06), a literatura que trata da execução de estratégias é um processo fragmentado e eclético (Noble, 1999a Sacramento et al (2015) A maneira como a execução é conduzida, por exemplo, diverge entre as organizações. Nutt de planos estratégicos não realizam plenamente suas expectativas e ambições devido à má implementação (Cândido & Santos, 2015). Os gestores percebem essa ineficiência.…”
Section: A Era Da Implementação Estratégicaunclassified
See 1 more Smart Citation